HUBUNGAN POWER OTOT TUNGKAI DAN OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN SHOOTING PADA TIM BOLA BASKET PUTRA SMP 6 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem found in this study is that not all of the members can shoot well. This is due to the weak leg muscle power and arm and shoulder muscle power of the students of SMP Negeri 6 Pekanbaru. This study aims to see the closeness of the relationship between leg muscle power and arm and shoulder muscle power to the shooting ability of the men's basketball team at SMP Negeri 6 Pekanbaru. This research was conducted at SMP Negeri 6 Pekanbaru. Held from May to October 2020. The population in this study was the men's basketball team at SMP Negeri 6 Pekanbaru, which numbered 12 people. The population in this study is relatively small, so all populations were sampled (total sampling) totaling 12 basketball players for the men's team at SMP Negeri 6 Pekanbaru. The results of this study, there is a strong relationship between leg muscle power and shoulder arm muscles with shooting ability, where r tab at a significant (0.05) = 0.602 means r count (0.982) > r tab (0.602), there is a relationship between leg muscle power and arm and shoulder muscle power with the shooting ability on the men's basketball team at SMP Negeri 6 Pekanbaru.Key Words: Power Of Leg Muscles And Arm And Shoulder Muscles, Shooting Ability